Water resources management and the law: comparative study between Kedah and Selangor state government / Razali Muhammad, Abd Rahman Ramli, Abd Hamid Abd Rahman. - Muhammad, Razali; Ramli, Abd Rahman; Abd Rahman, Abd Hamid (2010)
This research is a critical analysis on the differences in water resources management between the State of Kedah and Selangor after the amendment of the 9th Schedule in Federal Constitutional The establishment of Suruhanjaya Perkhidmatan Air Negara in 2006, under the provision of Water Service Commission Act and employs the Water Service Industry Act (WSIA) 2006 as regulatory tools to restructure the water resources management. The new system will ensure a more sustainable and efficient water supply service in Malaysia. However, since the land and water is under the jurisdiction State Authority on the State List,many conflict occurred between the Federal and State Government. This led to question, where is the significant and effectiveness of the WSIA 2006 in protecting the interst of the stakeholders in the Kedah and Selangor?. Malaysia had applies the unitary management and many agencies including the sState organization are involve play their function for water sustainability. However, there is no single agency entrusted with overall responsibility of holistic planning and management of water. Thus,this study was conducted on order to examine the differences in water resources management in Selangor and Kedah and the important of relevant regulatory body in both States.